2018
DOI: 10.1016/j.oret.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab Injection in Patients with Neovascular Age-Related Macular Degeneration Increases Angiogenic Biomarkers

Abstract: Purpose To evaluate the expression of 19 angiogenic biomarkers in the aqueous humor before and after intravitreal bevacizumab injection (IVB) in eyes with neovascular age-related macular degeneration (AMD). Design Prospective, noncomparative, interventional case series. Participants Twenty-three eyes of 23 treatment-naïve patients with choroidal neovascularization (CNV) secondary to neovascular AMD. Methods Eyes were diagnosed with CNV secondary to neovascular AMD and were treated with 3 monthly IVBs. Aq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 38 publications
(41 reference statements)
1
46
0
1
Order By: Relevance
“…33 In a previous study, there was no significant difference in the aqueous concentration of FGF-α between nAMD group and control group, but FGF-α concentration increased significantly after intravitreal injection of bevacizumab. 35 In our study, FGF-α concentration was significantly higher in nAMD patients before and after two consecutive monthly ranibizumab injections, in comparison to cataract patients, which deserves further study.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…33 In a previous study, there was no significant difference in the aqueous concentration of FGF-α between nAMD group and control group, but FGF-α concentration increased significantly after intravitreal injection of bevacizumab. 35 In our study, FGF-α concentration was significantly higher in nAMD patients before and after two consecutive monthly ranibizumab injections, in comparison to cataract patients, which deserves further study.…”
Section: Discussionmentioning
confidence: 49%
“…In a previous study, BMP-9 did not show any significant difference between nAMD and cataract group, and there was no difference after intravitreal injection of bevacizumab in nAMD patients. 35 Our study found higher expression of BMP-9 in the aqueous humor of nAMD patients, compared with cataract patients, which needs further research in the future.…”
Section: Discussionmentioning
confidence: 58%
“…53 Our observation indicates that the potential neurotoxic side effects of anti-VEGF therapy should not be overlooked because patients with nAMD and diabetic macular edema require a significant number of anti-VEGF injections in clinical practice. 30,[33][34][35] We acknowledge that our transgenic model may not recapitulate the full features of nAMD in humans. In our transgenic mice, subretinal new vessels actually originate from the retinal vasculature, 25 which is different from the choroidal origin of new vessels in nAMD.…”
Section: Discussionmentioning
confidence: 98%
“…endothelin 1, follistatin, heparin-binding epidermal growth factor (HB-EGF), hepatocyte growth factor (HGF), and IL8. 35,36 TGFb signaling plays an important role in fibrosis and neovascularization in multiple organs, but there is limited information about how it contributes to subretinal fibroneovascularization. TGFb signaling begins with the binding of TGFb superfamily ligands to the TGFb type II receptor, leading to activation of the TGFb type I receptor and phosphorylation of Smad proteins.…”
Section: Discussionmentioning
confidence: 99%
“…4 Despite its efficacy, a substantial number of patients (15%-20%) are intrinsically refractory to anti-VEGF treatment or may develop resistance over time, which is likely due to the compensatory activation of alternative angiogenic pathways. Indeed, hepatocyte growth factor (HGF) 5 and erythropoietin 6 were reported to be upregulated in eyes treated with anti-VEGF agents. Besides its role in angiogenesis, VEGF exerts a potent neuroprotective effect 7 and mediates vascular 8 and organ 9 homeostasis.…”
mentioning
confidence: 99%